SOSIALISASI LITERASI KEUANGAN DAN PENENTUAN HARGA JUAL PRODUK PADA UMKM INDUSTRI LOGAM SANJAYA TEKNIK - Latifa, Riza Sufia; Salsabila, Atika Zahra Nur; Adya, Cista Dilla; Roihatina, Gina; Nailussa’adah, Dini; Taufiqurrahman, Muhammad; Komando, Bima Arya; Pratama, Dika Wisnu; Lating, Ade Irma Suryani; Susanto, Febry Fabian (LPPM Universitas Nusa Mandiri, 2026)
MSMEs (Micro, Small, and Medium Enterprises) play a crucial role in the economy, particularly by creating job opportunities and fostering innovation that supports economic growth in both rural and urban areas. However, MSMEs often face classic challenges, such as low-quality human resources, limited technological adaptation, lack of access to capital information, and insufficient understanding of financial reporting. Capital is a critical factor, as business sustainability can be jeopardized without adequate access to funding. The MSME Sanjaya Teknik faces two main issues: a lack of financial literacy and the use of unsystematic methods for determining product selling prices. To address these issues, the team provided solutions through socialization and training on financial literacy, selling price calculations based on COGS (Cost of Goods Sold), and financial record-keeping. These activities were carried out in Ngingas District, Sidoarjo, using lectures, training sessions, and evaluations. The program comprised three phases: surveys and interviews, socialization and training sessions, and evaluations. As a result, Sanjaya Teknik's MSME owners now understand the importance of separating personal and business finances, maintaining structured financial records, and accurately determining product selling prices using Cost-Plus Pricing and Mark-Up Pricing methods. This initiative successfully enhanced the awareness of MSME owners about the importance of financial literacy for ensuring business sustainability.